Alexandre Parkhomenko (Leonid Loukov, 1942) : la guerre civile en Ukraine revue et corrigée - Eric Aunoble (Conserveries Mémorielles)
From June 22nd 1941, the Soviet state which was born from a revolutionary turmoil faced for the first time a full scale international war. As it was quickly named as “patriotic” by Stalin, this war saw a long lasting inflection of the Soviet discourse toward more nationalism. This could be felt also in movies. Hence, how the original revolutionary history would be linked with the new patriotic discourse? A focus on Leonid Lukov’s Alexandr Parkhomenko (1942) could help to see how the history of the 1918-21 Civil War was used and rewritten to serve the “Great Patriotic War” Soviet propaganda. Based upon four versions of the hero’s story issued by Vsevolod Ivanov between March 1939 and July 1942, this paper highlights the diplomatic, political and social constraints which shaped the movie as the public could eventually see it.